NCI Funding Trends and Priorities in Physical Activity and Energy Balance Research Among Cancer Survivors - Alfano, Catherine M; Bluethmann, Shirley M; Tesauro, Gina; Perna, Frank; Agurs-Collins, Tanya; Elena, Joanne W; Ross, Sharon A; O'Connell, Mary; Bowles, Heather R; Greenberg, Deborah; Nebeling, Linda (JNCI : Journal of the National Cancer Institute, 2016)
There is considerable evidence that a healthy lifestyle consisting of physical activity, healthy diet, and weight control is associated with reduced risk of morbidity and mortality after cancer. However, these behavioral interventions are not widely adopted in practice or community settings. Integrating heath behavior change interventions into standard survivorship care for the growing number of cancer survivors requires an understanding of the current state of the science and a coordinated scientific agenda for the future with focused attention in several priority areas. To facilitate this goal, this paper presents trends over the past decade of the National Cancer Institute (NCI) research portfolio, fiscal year 2004 to 2014, by funding mechanism, research focus, research design and methodology, primary study exposures and outcomes, and study team expertise and composition. These data inform a prioritized research agenda for the next decade focused on demonstrating value and feasibility and creating desire for health behavior change interventions at multiple levels including the survivor, clinician, and healthcare payer to facilitate the development and implementation of appropriately targeted, adaptive, effective, and sustainable programs for all survivors.